2016
DOI: 10.18632/oncotarget.7828
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNAs as prognostic markers in human breast cancer

Abstract: Long non-coding RNAs (lncRNAs) have been recently shown to play an important role in gene regulation and normal cellular functions, and disease processes. However, despite the overwhelming number of lncRNAs identified to date, little is known about their role in cancer for vast majority of them. The present study aims to determine whether lncRNAs can serve as prognostic markers in human breast cancer. We interrogated the breast invasive carcinoma dataset of the Cancer Genome Atlas (TCGA) at the cBioPortal cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
149
2
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(159 citation statements)
references
References 48 publications
7
149
2
1
Order By: Relevance
“…So far, an overwhelming number of lncRNAs have been identified89, and a certain subset of lncRNAs have been found to play critical roles in oncogenesis and tumor progression10111213. Increasing evidences indicate that, in many types of cancers, lncRNAs are aberrantly expressed and are involved in regulation of diverse biological functions1415161718, suggesting their potential as biomarkers for cancer. Moreover, recent reports181920 have uncovered the potential of lncRNAs as biomarkers for clinical outcomes in many cancers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…So far, an overwhelming number of lncRNAs have been identified89, and a certain subset of lncRNAs have been found to play critical roles in oncogenesis and tumor progression10111213. Increasing evidences indicate that, in many types of cancers, lncRNAs are aberrantly expressed and are involved in regulation of diverse biological functions1415161718, suggesting their potential as biomarkers for cancer. Moreover, recent reports181920 have uncovered the potential of lncRNAs as biomarkers for clinical outcomes in many cancers.…”
mentioning
confidence: 99%
“…Increasing evidences indicate that, in many types of cancers, lncRNAs are aberrantly expressed and are involved in regulation of diverse biological functions1415161718, suggesting their potential as biomarkers for cancer. Moreover, recent reports181920 have uncovered the potential of lncRNAs as biomarkers for clinical outcomes in many cancers. However, the possible roles and prognostic values of lncRNA signature and specific lncRNAs have not been elucidated clearly in PTC.…”
mentioning
confidence: 99%
“…Liu et al also identified 11 dysregulated lncRNAs, based mainly on their CNAs, which were associated with poor OS in breast cancer. Of these lncRNAs, LINC00657 lncRNA knockout was shown to suppress breast cancer cell growth and proliferation [52], indicating its oncogenic role. Collectively, these data reveal that genetic variants of lncRNAs may serve functional and predictive roles, despite some inconsistent results that urge further study in large cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…As lncRNAs do not code for proteins, lncRNA expression may be a better indicator of the tumor status, implying the potential and superiority as independent biomarkers for early diagnosis and prognosis prediction in cancers [29]. Currently, several expression-based lncRNA signature have been identified to predict patients' survival in some cancers, including glioblastoma multiforme [30], oesophageal squamous cell carcinoma [31], colorectal cancer [32], breast cancer [3335], lung cancer [36] and multiple myeloma [37]. Recent studies have revealed that changes in lncRNA expression were associated with OvCa tumorigenesis and metastasis.…”
Section: Introductionmentioning
confidence: 99%